THE INFLUENCE OF SOCIAL MEDIA MARKETING, BRAND IMAGE, AND PRICE PERCEPTION ON PURCHASE INTENTION OF MS GLOW SKINCARE IN SURABAYA - Eva Dwi Krinawati,; Endang Setyowati, (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
This study aims to analyze the effect of social media marketing, brand images, perceived price has an effect on purchase intantions of skincare products Ms Glow, skincare in Surabaya Quantitative descriptive research is a type of research aimed at describing or explaining the characteristics of a phenomenon in a systematic and measurable way. This research uses data in the form of numbers (quantitative) and statistical analysis to identify patterns, relationships, or certain trends. Data collection is conducted through measurable instruments such as questionnaires, surveys, or quantifiable forms. Statistical analysis is used in data processing to present a clearer picture or description. The depiction of relationships between variables is done without intervention. The population of this research consists of MS Glow skincare users, and the sampling technique used is purposive sampling with a sample of 100 respondents who are MS Glow skincare users in Surabaya. The data analysis methods employed are multiple linear regression analysis, t-test, and f-test. The results of the study indicate that the social media marketing variable has a significant effect on the purchase intention of MS GLOW skincare, brand image has a significant effect on the purchase intention of MS GLOW skincare, and price perception has a significant effect on the purchase intention of MS GLOW skincare.